Physical and Functional Interactions of Human DNA Polymerase η with PCNA - Haracska, Lajos (American Society for Microbiology, 2001)
Human DNA polymerase η (hPolη) functions in the error-free replication of UV-damaged DNA, and mutations in hPolη cause cancer-prone syndrome, the variant form of xeroderma pigmentosum. However, in spite of its key role in promoting replication through a variety of distorting DNA lesions, the manner by which hPolη is targeted to the replication machinery stalled at a lesion site remains unknown. Here, we provide evidence for the physical interaction of hPolη with proliferating cell nuclear antigen (PCNA) and show that mutations in the PCNA binding motif of hPolη inactivate this interaction. PCNA, together with replication factor C and replication protein A, stimulates the DNA synthetic activity of hPolη, and steady-state kinetic studies indicate that this stimulation accrues from an increase in the efficiency of nucleotide insertion resulting from a reduction in the apparent K(m) for the incoming nucleotide.